Politécnicos ou matemáticos? Polytechnicians or mathematicians? - Circe Mary da Silva (História, Ciências, Saúde: Manguinhos, 2006)
As primeiras pesquisas matemáticas no Brasil foram realizadas por pessoas com formação politécnica, isto é, oriundos das Escolas Politécnicas. Este trabalho apresenta esboços biográficos e as principais contribuições de onze desses(as) pioneiros(as), que atuaram em escolas militares e politécnicas e nas faculdades de filosofia que surgiram a partir da década de 1930, no país. Diferencia-se o grupo dos onze matemáticos(as) entre os simpatizantes e os(as) não-simpatizantes do positivismo. The first mathematics research were realized in Brazil by people with polytechnical formation, that means, coming from Polytechnic . This work presents biographical drafts and the main contributions of elevens from these pioneers. The worked in military Schools and Polytechnic. And also in the faculties of philosophy that started to appear in the country since 1930. In these group of eleven mathematicians one can differentiated between the ones who were sympathetic with positivism and the ones who were not.